2015
DOI: 10.4066/amj.2015.2460
|View full text |Cite
|
Sign up to set email alerts
|

Utility of cord blood culture in early onset neonatal sepsis

Abstract: UCBC is a simple convenient method, which ensures culture of adequate volume of blood from newborns allowing effective early isolation of bacterial pathogens, especially in EONS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Another study evaluating 40 neonates with two or more risk factors for EOS found that, compared with peripheral venous samples, cord blood had 100% sensitivity and 95% specificity (27). Cord blood CRP, however, was negative in all 11 neonates who screened positive for sepsis (27).…”
Section: Novel Diagnostic Approaches To Neonatal Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Another study evaluating 40 neonates with two or more risk factors for EOS found that, compared with peripheral venous samples, cord blood had 100% sensitivity and 95% specificity (27). Cord blood CRP, however, was negative in all 11 neonates who screened positive for sepsis (27).…”
Section: Novel Diagnostic Approaches To Neonatal Sepsismentioning
confidence: 99%
“…review of 15 studies evaluating over 2,000 episodes of suspected neonatal infection identified interleukin-6 (IL-6) and PCT in cord blood as having high positive (9.47 and 5.72, respectively) and negative likelihood ratios (0.10 and 0.20, respectively) (22). Another study evaluating 40 neonates with two or more risk factors for EOS found that, compared with peripheral venous samples, cord blood had 100% sensitivity and 95% specificity (27). Cord blood CRP, however, was negative in all 11 neonates who screened positive for sepsis (27).…”
Section: Novel Diagnostic Approaches To Neonatal Sepsismentioning
confidence: 99%
“…19 The sensitivity of cord blood culture is 80-100% and specificity is 91-94%, while the positive and negative predictive value are 33-72% and 94-100%, respectively. 19,20 It is less invasive and painful, easier to preform, and a larger volume of blood is available compared with peripheal blood cultures. A good technique will reduce the risk of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…La técnica de recolección de HC de cordón es crítica, pues existe alto riesgo de contaminación post parto vaginal 33,34 . Los principales beneficios que ofrece esta técnica son: • Obtención inmediata de la muestra, sin retrasar el diagnóstico y permitiendo rápidamente el inicio de antimicrobianos empíricos en niños con sospecha de sepsis precoz.…”
Section: Hemocultivos De Cordónunclassified
“…Se realizó una desinfección del extremo placentario con alcohol 70º y se recolectó una muestra de sangre de 2 ml, que fueron sembrados en una botella de HC aeróbico. La sensibilidad de este método en este estudio fue de 100% con una especificidad de 94,9% en comparación con los HC tomados en vena periférica 34 . Por otra parte, existen otros reportes que describen una sensibilidad un poco menor, cercanas a 80%, con especificidad de 91,4% comparadas con HC tomados por vía periférica 36 .…”
Section: Hemocultivos De Cordónunclassified